Hydrothermal Synthesis of Cu@C Composite Spheres by a One‐Step Method and Their Use as Sacrificial Templates to Synthesize a CuO@SiO2 Core–Shell Structure. Issue 28 (30th July 2013) - Cheng, Yi; Niu, Xiaoyu; Zhao, Tieying; Yuan, Fulong; Zhu, Yujun; Fu, Honggang
Abstract: Cu@C composite spheres with copper nanoparticles dispersed in the carbonaceous matter have been synthesized by a one‐step hydrothermal method by using different copper salts mixed with an aqueous glucose solution. The spheres have been characterized by X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, thermogravimetric–differential thermal analysis, inductively coupled plasma atomic emission spectrometry, Fourier transform infrared spectroscopy, and Raman spectrocopy. The results show that Cu(NO3 )2, CuSO4, and CuCl2 exhibit an accelerating effect on the size of the composite spheres, and microsized composites were obtained. However, a morphological change from irregular cubes and spheres to uniform spheres with a narrow size distribution of 340–400 nm was observed when cupric acetate [Cu(Ac)2 ] was used. Interestingly, Cu2 O, generated in situ from Cu(ac)2, plays an important role in the size of the composite spheres. Moreover, a CuO@SiO2 core–shell structure has been synthesized by using the Cu@C composite spheres as a sacrificial template, and the CO + NO reaction was used as a probe reaction to evaluate its catalytic performance. CuO@SiO2 exhibits excellent catalytic performance in the CO + NO reaction. Abstract : Submicron Cu@C composite spheres are synthesized by a facile one‐step hydrothermal method and used to prepare a CuO@SiO2 core–shell structure that shows excellent catalytic performance in the CO + NO reaction.